Spatial analysis of blackfly in agroforestry system of citrus - Silva, Anderson Gonçalves; Farias, Paulo Roberto Silva; Boiça Junior, Arlindo Leal; Lima, Bruno Gonçaves; Ponte, Nara Helena Tavares da; Pinho, Raphael Coelho; Barbosa, Ronny Sobreira (Comunicata Scientiae, 2015)
The aim of this study was to characterize the spatial distribution of citrus black fly (Aleurocanthus woglumi) in citrus orchard in agroforestry plantation in Pará State, Brazil. The experimental area is located in Capitão Poço, Northeastern Pará. Twelve samples were taken monthly where the presence or absence of the pest in the experimental area were evaluated. From each sampling point (plant) we obtained the value of the variable and the coordinates (latitude and longitude). By the parameters of semivariogram models the surveys were interpolated by kriging method which provided us spatial distribution maps of the areas of higher and lower infestation of the black fly. The results showed that the spatial distribution of black fly takes place predominantly in clusters with spatial dependence described by the spherical model, forming clusters from 15.5 to 34 m (range of the model).